In-Line Nanostructuring of Glass Fibres Using Different Carbon Allotropes for Structural Health Monitoring Application - Michael Thomas Müller; Kristina Eichhorn; Uwe Gohs; Gert Heinrich (Fibers, 2019)
By the in-line nanostructuring of glass fibres (GF) during the glass fibre melt spinning process, the authors achieve an electro-mechanical-response-sensor. The glass fibre interphase was functionalized with different highly electrically conductive carbon allotropes such as carbon nanotubes, graphene nanoplatelets, or conductive carbon black. On-line structural health monitoring is demonstrated in continuous glass fibre-reinforced polypropylene composites during a static or dynamic three-point bending test. The different carbon fillers exhibit qualitative differences in their signal quality and sensitivity due to the differences in the aspect ratio of the nanoparticles, the film homogeneity, and the associated electrically conductive network density in the interphase. The occurrence of irreversible signal changes during dynamic loading may be attributed to filler reorientation processes caused by polymer creeping or to the destruction of the electrically conductive paths due to the presence of cracks in the glass fibre interphase. Further, the authors found that sensor embedding hardly influences the tensile properties of continuous GF reinforced polypropylene (PP) composite.